2014
DOI: 10.1016/j.sbspro.2014.09.101
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Reaction for Scoring on Corporate Governance

Abstract: There is a widely heralded need for improved corporate governance practices in order to stave off potential turbulences in financial markets. Corporate governance index enables investors to monitor the compliance level of firms with corporate governance principles. This study attempts to examine whether the market players in Borsa İstanbul recognize the value of getting a corporate governance score in the period of 2007 and 2013. The initial evidence supports that the market players value the scoring and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…They found the direct positive link of the score of corporate governance with the listed companies' share prices [50]. An interesting study was conducted to measure the response of share prices to corporate governance score announcement results between 2007 and 2013, and they found a sharp positive change in share prices during the first announcement day [51]. Recent studies have focused on various aspects of corporate governance and its relationship with the sustainable development of the entire industry and economy.…”
Section: Corporate Governance Structure and Firms Performancesmentioning
confidence: 99%
“…They found the direct positive link of the score of corporate governance with the listed companies' share prices [50]. An interesting study was conducted to measure the response of share prices to corporate governance score announcement results between 2007 and 2013, and they found a sharp positive change in share prices during the first announcement day [51]. Recent studies have focused on various aspects of corporate governance and its relationship with the sustainable development of the entire industry and economy.…”
Section: Corporate Governance Structure and Firms Performancesmentioning
confidence: 99%
“…The test results show that the corporate governance index has a positive effect on stock return. The results of these studies were confirmed by Rogers, Riberio, and Securato (2008); Parigi, Pelizon and von Thadden (2013); and Teker and Yuksel (2014). The results of these studies indicate that governance is considered positive by the market.…”
mentioning
confidence: 54%
“…Empirical evidence finds a direct correlation between good CG and the firm's share prices in Pakistan, as well as that different levels of CG have different links with the firm's share prices and performance (PeiZhi and Ramzan, 2020). Teker and Yüksel (2014) observe a sharp positive movement in share prices on the first day of the announcement in Turkey.…”
Section: Literature Reviewmentioning
confidence: 87%